Spatial Correlation Analysis on the Resource Allocation Efficiency of Regional Higher Education in China - Li Yuanjing; Wang Chengzhang (Journal of Education and Learning (EduLearn), 2013)
This analysis may promote the regional development of higher education, resolve problems associated with inadequate resources, and improve efficiency of resource allocation. In this study, we examined the efficiency of resource allocation for higher education in 31 Chinese provinces using data envelopment analysis (DEA); spatial correlation was used concurrently for analytical purposes. Our aims through this study are to promote the optimal allocation of resources and healthy development of higher education.